Implementation of Air Sweep to Prevent Blockages on The Salt Crystallization Process - Heru Mirmanto; Arino Anzip; Dedy Zulhidayat; Joko Sarsetiyanto (Institut Teknologi Sepuluh Nopember, 2024)
In the process of crystallization salt, blockages often occur due to the large amount of salt that sticks to the wall’s hopper of the crusher machine. Seeing this condition, a Salt Cleaning Tool was designed using the air sweep method. In the first step of the design, a survey was carried out to find out how thick and the area of salt that sticks over a certain period. Furthermore, experiments were carried out to determine the position of the nozzle and the air pressure needed to knock out the salt attached to the hopper. The control system uses Arduino hardware as a micro controller tool. The experimental results require that the spray direction is tangential to the hopper surface, so the nozzle on the market needs to be modified. Likewise, an air pressure of 6 bar .is required and a burst time period of every 3 seconds with a nozzle opening time of 250 milliseconds with the condition that three solenoids are open together. Modification of the nozzle The control system uses Arduino hardware as a micro controller tool. The implementation of the air sweep as a salt cleaning tool has been successful, this is evidenced by operation of the crusher machine without problems.